1996
DOI: 10.1177/036354659602400218
|View full text |Cite
|
Sign up to set email alerts
|

Patellar Height Ratios

Abstract: Three blinded observers on three separate occasions calculated four commonly employed patellar height ratios on the knees of 15 patients who had three lateral radiographs each. The observers used the same measurement instrument, a hand-held goniometer ruler, to determine the relative reliability of each patellar height ratio. The measurements by the three observers were examined, and the error and reliability of the four methods of measurement were tested statistically. Among the four methods of measuring pate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(45 citation statements)
references
References 12 publications
0
41
1
3
Order By: Relevance
“…The impact of skeletal maturity has sometimes also been assessed. In many cases, these analyses have used radiographs on abnormal or diseases knees 15 , 17 , 19 , 20 , 21 , 22 . Even fewer studies have compared inter-observer concordance between the commonest methods for measuring patellar height in normal knees, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of skeletal maturity has sometimes also been assessed. In many cases, these analyses have used radiographs on abnormal or diseases knees 15 , 17 , 19 , 20 , 21 , 22 . Even fewer studies have compared inter-observer concordance between the commonest methods for measuring patellar height in normal knees, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[51314] These methods evaluate the patella height indirectly according to various tibial reference points. [15] Numerous studies have compared these measurement methods, and different authors have emphasised the various advantages of the different methods.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Numerous studies have compared these measurement methods, and different authors have emphasised the various advantages of the different methods. [71011121314] Over time, taking other indices into consideration, modifications have been made to some of the indices themselves, such as for the Insall–Salvati index, which has been updated as the modified Insall–Salvati index.…”
Section: Discussionmentioning
confidence: 99%
“…They also warned that measurements using the Blackburne and Peel and the Caton and Deschamps indices are also abnormal in cases of low pseudo-patella (18) , and thus should not be used in isolation to determine the retraction of the patellar tendon. Barnett et al (3) suggested that because these are indices that use a line traced out by the tibial plateau, they may lead to reduced accuracy 34 , 35 , 36 .…”
Section: Discussionmentioning
confidence: 99%